Research priorities in fragility fractures of the lower limb and pelvis: a UK priority setting partnership with the James Lind Alliance. Issue 10 (3rd October 2018) - Fernandez, Miguel A; Arnel, Laura; Gould, Jenny; McGibbon, Alwin; Grant, Richard; Bell, Philip; White, Stuart; Baxter, Mark; Griffin, Xavier; Chesser, Tim; Keene, David; Kearney, Rebecca S; et al.
Abstract : Objective: To determine research priorities in fragility fractures of the lower limb and pelvis which represent the shared priorities of patients, their friends and families, carers and healthcare professionals. Design/setting: A national (UK) research priority setting partnership. Participants: Patients over 60 years of age who have experienced a fragility fracture of the lower limb or pelvis; carers involved in their care (both in and out of hospital); family and friends of patients; healthcare professionals involved in the treatment of these patients including but not limited to surgeons, anaesthetists, paramedics, nurses, general practitioners, physicians, physiotherapists and occupational therapists. Methods: Using a multiphase methodology in partnership with the James Lind Alliance over 18 months (August 2016–January 2018), a national scoping survey asked respondents to submit their research uncertainties. These were amalgamated into a smaller number of research questions. The existing evidence was searched to ensure that the questions had not been answered. A second national survey asked respondents to prioritise the research questions. A final shortlist of 25 questions was taken to a multistakeholder workshop where a consensus was reached on the top 10 priorities. Results: There were 963 original uncertainties submitted by 365 respondents to the first survey. These original uncertainties were refined into 88 research questions of which 76 were judged to be true uncertainties following a review of the research evidence. Healthcare professionals and other stakeholders (patients, carers, friends and families) were represented equally in the responses. The top 10 represent uncertainties in rehabilitation, pain management, anaesthesia and surgery. Conclusions: We report the top 10 UK research priorities in patients with fragility fractures of the lower limb and pelvis. The priorities highlight uncertainties in rehabilitation, postoperative physiotherapy, pain, weight-bearing, infection and thromboprophylaxis. The challenge now is to refine and deliver answers to these research priorities.